Perbandingan Metode SYBR Green dan Hydrolysis Probe dalam Analisis DNA Gelatin Sapi dan Gelatin Babi Menggunakan Real Time Polymerase Chain Reaction - Zilhadia Zilhadia; Afifah Nurul Izzah; Ofa Suzanti Betha (Fakultas Farmasi Universitas Andalas, 2017)
Gelatin has a large application in the food, pharmaceutical and cosmetics industries. Gelatin is mostly derived from the skin or bone of porcine and bovine. Porcine gelatin is forbidden for Muslim and Jews. For this reason, analytical methods to detect gelatin are needed to make sure the source of gelatin. One of the analytical techniques that can differentiate bovine and porcine gelatin is Real Time Polymerase Chain Reaction (PCR). There are two popular methods of fluorescence dye, namely SYBR green and hydrolysis probe. This study was conducted to compare SYBR green and hydrolysis probe method in analyzing porcine and bovine gelatin DNA using Real Time PCR. The DNA was isolated by commercial kit. The obtained porcine and bovine gelatin DNA were 19.38 ng/μl and 13.63 ng/μl with purity were 1,566 and 1,573, respectively. Then, isolated DNA was analyzed by SYBR green and hydrolysis methods. SYBR green methods was done by annealing temperature of 65 oC for bovine primer and 60 oC for porcine primer. Therefore, hydrolysis probe methods were analyzed by annealing temperature of 60 oC for both porcine primer and bovine primer. The result showed that the hydrolysis probe was higher specificity to identify of porcine and bovine gelatin DNA than SYBR green method.